2022
DOI: 10.3390/atmos13020313
|View full text |Cite
|
Sign up to set email alerts
|

First Long-Time Airborne Fungal Spores Study in Dublin, Ireland (1978–1980)

Abstract: Ambient fungal spores within the atmosphere can contribute to a range of negative human, animal and plant health conditions and diseases. However, trends in fungal spore seasonality, species prevalence, and geographical origin have been significantly understudied in Ireland. Previously unpublished data from the late 1970s have recently been collected and analysed to establish historical fungal spore trends/characteristics for Dublin. Historical spore concentrations were largely dominated by Alternaria, Ascospo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
5
5
0
Order By: Relevance
“…Cladosporium was the most abundant airborne fungal spore in this study, a feature found to be characteristic of a temperate climate (D'Amato and Spieksma, 1995) and observed in many studies across Europe (Antón et al, 2019;Kasprzyk et al, 2004;Martínez-Bracero et al, 2022;Sadys et al, 2016a;Scevkova and Kovac, 2019;Vélez-Pereira et al, 2021).…”
Section: Fungal Spore Seasonssupporting
confidence: 63%
See 1 more Smart Citation
“…Cladosporium was the most abundant airborne fungal spore in this study, a feature found to be characteristic of a temperate climate (D'Amato and Spieksma, 1995) and observed in many studies across Europe (Antón et al, 2019;Kasprzyk et al, 2004;Martínez-Bracero et al, 2022;Sadys et al, 2016a;Scevkova and Kovac, 2019;Vélez-Pereira et al, 2021).…”
Section: Fungal Spore Seasonssupporting
confidence: 63%
“…While much research has focused on the creation of pollen seasonal calendars to aid allergen avoidance, the same cannot be said in relation to annual fungal spore distributions. Studies that put forward fungal spore calendars specifically have tended to study just one or two spore genera or phyla (Antón et al, 2019; Elvira-Rendueles et al, 2019; Sánchez Reyes et al, 2022) or to sample for less than the 5 years recommended by the European Aerobiological Society (Antón et al, 2019; Bednarz and Pawłowska, 2016; Galan et al, 2017; Kasprzyk et al, 2004; Martínez-Bracero et al, 2022; Reyes et al, 2016; Scevkova and Kovac, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This study represents the first comprehensive, multi-season survey of airborne pollen in Ireland. Prior to this, some short-term pollen (McDonald, 1980;McDonald & O'Driscoll, 1980) and Fungal spore (Healy et al, 2014;Martínez-Bracero et al, 2022;O'Connor et al, 2015aO'Connor et al, , 2015bO'Connor et al, , 2014aO'Connor et al, , 2014b monitoring campaigns were conducted, but none were designed for the continuous or long-term monitoring of pollen trends or for identifying any changes within the network over time. Given that not many previous studies have taken place in Ireland, the few that have been carried out were analysed to identify possible similarities or differences with the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The worst conditions were experienced from the 28th of February to the 4th of March with air and ground temperatures 5 to 10° below normal (Government of Ireland and Met Éireann, 2019 ). Studies have highlighted that early springtime conditions such as temperature are deciding factors for plant development and thus pollen production (Matyasovszky et al, 2015 ). As a result, the expected release of arboreal pollen in late March was significantly reduced as was the summer release of Poaceae pollen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation